Educational process in the context of innovative development of lifelong education: main features and prospects - Mykhaylyova , K. (New Collegium, 2021)
The article is devoted to the consideration of the main elements of the educational process in the experimental complex of continuing education, thanks to which the high quality of education and key positions in the international rankings of universities are achieved. It is shown that the basic principles underlying the organization of the educational process can be divided into three groups: basic methodological (these include the principles of continuity, humanism and democracy, tolerance, collectivism and command, system, science, activity), organizational and methodological (partnerships, continuity of learning, research and education, innovation, providing conditions for independent learning and creativity, academic freedom, openness and transparency, individualization, academic integrity) and social context (compliance with national and international standards, competitiveness, elitism, equal access to education programs, social partnership, compliance with modern trends). The introduction of innovative approaches to the organization of the educational process, in particular distance learning technologies, game technologies, mechanisms for choosing disciplines and recognition of the results of non-formal and informal education, etc. is demonstrated. Emphasis is placed on the involvement of various categories of subjects in the educational process, including visiting professors, employers, practitioners, etc. The effectiveness of ensuring the quality of the educational process through the results of PUA participation in the international ranking MULTIRANK-2020 is shown.